NILAI-NILAI KARAKTER KEMANDIRIAN, KERJA KERAS, KREATIF DAN DEMOKRASI DALAM SERAT WEDATAMA - Sulastri; Nyoman Dantes; Relin D.E (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2023)
Rapid technological advancements facilitate human progress towards various objectives, but they also have a drawback, namely the emergence of instant culture. All things desire to be quick, simple, helpful, and satisfying. A culture that is averse to effort, care, and empathy will become hardworking due to this character. The life guidance derived from regional culture and beliefs must be rebuilt. A literary piece called Serat Wedatama, which takes the form of a macapat song, contains moral lessons. It is essential to continuously work towards fostering self-discipline, perseverance, creativity, independence, and democracy founded on sincerity, patience, and sincerity. It is possible to purify the heart and mind through selfless work, which affects behaviour that is not constrained by professional outcomes. An incentive to put in the extra effort will be a disciplined character that has become ingrained. Genuinely working hard and dedicating all of one's creations and emotions will yield satisfying results. The ability or self-intuition that generates creative ideas will awaken with sincere effort. A sense of self-confidence fostered by creative ideas can help someone become independent. Coexisting in various societal contexts is also a necessary component of independence. Humans must cooperate while putting mutual respect and appreciation first in order to establish democracy in a society with a variety of conditions and characters.